HUBUNGAN MEKANISME KOPING DENGAN KUALITAS HIDUP PADA PENDERITA DIABETES MELITUS TIPE 2 - Rosliana Dewi; Inten Herlianti Anugrah; Iwan Permana; Johan Budhiana; Fera Melinda (JURNAL KESEHATAN INDRA HUSADA, 2021)
Diabetes mellitus complications affect the quality of life of the client. The use of positive coping mechanisms in people with diabetes mellitus can reduce stress, cause a decrease in blood sugar levels in diabetes mellitus sufferers so that they can maintain a good quality of life. To determine the relationship of coping mechanisms with quality of life in people with type 2 diabetes mellitus. This research uses a correlational research type and a cross sectional approach involving 41 respondents, the COPE and DQOL The Brief online questionnaire. Chi squared was used to analyze data. Most of the coping mechanisms in type 2 diabetes mellitus sufferers had maladaptive for 21 people (51.2%), and moderate quality of life for 17 people (41.4%). There is a significant correlation between coping mechanisms and quality of life p-value of 0.003 (α> 0.05). The coping mechanism affects the quality of life of people with mellitus type 2, efforts that can be made by providing education regarding the importance of coping mechanisms for sufferers and their families in order to optimize the coping mechanism, so that it has a better impact on blood sugar control.